Climate-challenged society - Dryzek, John S. (Oxford Oxford University Press, 2013)
This book is an original, accessible, and thought-provoking introduction to the severe and broad-ranging challenges that climate change presents and how societies can respond. It synthesizes and deploys cutting-edge scholarship on the range of social, economic, political, and philosophical issues surrounding climate change. The treatment is introductory, but the book is written "with attitude", for nobody has yet charted in coherent, integrative, and effective fashion a way to move societies beyond their current paralysis as they face the challenges of climate change.
Includes bibliographical references (p. 149-163) and index.
Keywords: Climatic changes --Social aspects